"GREEN ECONOMY - THE KEY TO SUSTAINABLE DEVELOPMENT FOR THE FUTURE" (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This thesis examines the green economy's role in promoting sustainable development in the 21st century. It highlights principles like renewable energy, sustainable agriculture, and efficient resource management, and their effects on economic resilience and social welfare. Through case studies, it showcases effective strategies and emphasizes the need for innovative financing and public-private collaboration. Ultimately, it argues that a green economy is essential for mitigating environmental threats and achieving sustainability goals.